Answer:
2x + 5y = - 15
Step-by-step explanation:
The line that passes through (–5, –1) and (10, –7) points and the point-slope form of the equation is
.
Now, we have to arrange this in the standard form.
So, ![y + 7 = - \frac{2}{5}(x - 10)](https://tex.z-dn.net/?f=y%20%2B%207%20%3D%20-%20%5Cfrac%7B2%7D%7B5%7D%28x%20-%2010%29)
⇒ 5(y + 7) = - 2(x - 10)
⇒ 5y + 35 = - 2x + 20
⇒ 2x + 5y = - 15 (Answer)
Answer: ![\frac{\sqrt{6}}{5y}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B6%7D%7D%7B5y%7D)
Step-by-step explanation:
The given radical expressions are:
![A. \frac{11y}{\sqrt{3}}\\\text{It is not completely simplified ,}\\\text{since denominator is radical, we need to rationalize it first to simplify. }\\\\B.\frac{\sqrt{6}}{5y}\\\text{It is completely simplified ,}\\\text{since its denominator is not radical and 6 is not a perfect square. }\\\\C. \frac{\sqrt{17}}{\sqrt{4}}\\\text{It is not completely simplified ,}\\\text{since denominator is radical, we need to rationalize it first to simplify. }\\\\](https://tex.z-dn.net/?f=A.%20%5Cfrac%7B11y%7D%7B%5Csqrt%7B3%7D%7D%5C%5C%5Ctext%7BIt%20is%20not%20completely%20simplified%20%2C%7D%5C%5C%5Ctext%7Bsince%20denominator%20is%20radical%2C%20we%20need%20to%20rationalize%20it%20first%20to%20simplify.%20%7D%5C%5C%5C%5CB.%5Cfrac%7B%5Csqrt%7B6%7D%7D%7B5y%7D%5C%5C%5Ctext%7BIt%20is%20completely%20simplified%20%2C%7D%5C%5C%5Ctext%7Bsince%20its%20denominator%20is%20not%20radical%20and%206%20is%20not%20a%20perfect%20square.%20%7D%5C%5C%5C%5CC.%20%5Cfrac%7B%5Csqrt%7B17%7D%7D%7B%5Csqrt%7B4%7D%7D%5C%5C%5Ctext%7BIt%20is%20not%20completely%20simplified%20%2C%7D%5C%5C%5Ctext%7Bsince%20denominator%20is%20radical%2C%20we%20need%20to%20rationalize%20it%20first%20to%20simplify.%20%7D%5C%5C%5C%5C)
![\\\\D. \frac{\sqrt{25}}{18}=\frac{5}{18}\\\text{Hence, expression D was not completely simplified .}](https://tex.z-dn.net/?f=%5C%5C%5C%5CD.%20%5Cfrac%7B%5Csqrt%7B25%7D%7D%7B18%7D%3D%5Cfrac%7B5%7D%7B18%7D%5C%5C%5Ctext%7BHence%2C%20expression%20D%20was%20not%20completely%20simplified%20.%7D)
Step-by-step explanation:
X=e+r/d
swap both sides
e+r/d=x
subtract e from both sides
e-e+r/d=x-e
r/d=x-e
multiply d to both sides
d×r/d=x-e×d
r=x-e×d
Well do you know a common factor between 8, 5, and 12, if so it is super simple to find your answer. :)